Psychometric Properties of the Job Related Skills Inventory in Malaysia Context - Chua Bee Seok; Getrude C. Ah Gang @ Grace; Shazia Iqbal Hashmi; Norhamidah Jarimal @ Safri; Agnis Sombuling (THEIJSSHI, 2020)
The objectives of the current study were to test the internal consistency, convergent and discriminant validity and item analysis of the Job-Related Skills Inventory in the Malaysian context. The study was conducted among 102 employers from the various government departments in Sabah, Malaysia. Cronbach alphas calculated to assess the inventory internal consistency of the inventory. The evidence for convergent validity of the inventory was tested by examining the inter-correlation between sub-aspect of the skills and correlation between the sub-aspects and the four dimensions of Industrial Revolution job-related skill. The discriminant validity of the Inventory was determined by examining the correlation between the inventory score and the scores of the Short Social Desirability Scale. Item analysis was also conducted to test the suitability and gaugeable of the Job-Related Skills Inventory items in the Malaysian context. The scale demonstrated good internal consistency (Cronbach alpha ranged from 0.87 to 0.95). The result reported The Job-Related Skills Inventory convergent and discriminant validity was confirmed with the strong relationship among the Inventory dimensions and strong relationship with the four dimensions of Industrial Revolution job-related skill as compared to weak and negative correlation coefficients between the inventory and the Social Desirability Scale. The result of item analysis also indicated all the items were good and suitable to use in the Malaysian context.